Effect of promotional tools towards sales at Tenaga Nasional Berhad (TNB) Port Dickson among the domestic customer / Muhammad Asyraff Sulaiman - Sulaiman, Muhammad Asyraff (Faculty of Business and Management, 2015)
This research is about the effect of promotional tools towards sales at Tenaga Nasional Berhad Port Dickson among the domestic customer. the problem statement in this research is why the sales increase at Tenaga Nasional Berhad Port Dickson. There are four research objective in this research which are to identify the level of the sales at Tenaga Nasional Berhad Port Dickson, to determine relationship between promotional tools and sales at Tenaga Nasional Berhad Port Dickson, to seek the most dominant promotional tool towards sales at Tenaga Nasional Berhad Port Dickson and to identify the alternatives to improve sales at Tenaga Nasional Berhad Port Dickson. For the research methodology the domestic customer was used as the respondent. the method of sampling design is non-probability sampling method and the technique that been use is convenience sampling. for the findings, this research is to test the reliability for the cronbach’s alpha, find the respondent profile, find the level of sales at Tenaga Nasional Berhad Port Dickson, identify the relationship between promotional tools and sales or the correlations whether it is significant or not significant and the last finding is the most dominant promotional tools or the coefficients.